Growing Lettuce in Small Hydroponic Systems: HS1422, 9/2021 - Sandoya, Germán V.; Bosques, Jonael; Rivera, Francisco; Campoverde, E. Vanessa (EDIS, 2021)
This new 6-page publication of the UF/IFAS Horticultural Sciences Department presents an overview on the use of different small hydroponic systems that could be implemented by home gardeners for lettuce. Recommendations on lighting, media, and other key aspects are presented in this publication as well. Written by Germán V. Sandoya, Jonael Bosques, Francisco Rivera, and E. Vanessa Campoverde.